Editorial Notes - Ab Wahid, Hariyaty (International Business Education Journal, 2025)
The International Business Education Journal (IBEJ), Volume 18, Issue 1 (2025), proudly features a diverse range of scholarly articles that reflect current perspectives, trends, practices and challenges in business education, economics, finance, social sciences and education around the globe. This volume comprises ten articles written by diverse prolific authors from Malaysia, Nigeria, the Philippines and the UAE.